The Semi-Graphic Method of Analysis for 7 Days of Tidal Observations - Franco, A. Dos Santos (The International Hydrographic Review, 2015)
In the Admiralty Tidal Handbook No. 3 Commander Suthons has just developed a semi-graphic method of harmonic analysis of tides for observation periods as short as 24 hours. The author considers one week’s hourly observations as in fact a set of groups of 24-hour observations whose analysis requires that the relations between the principal constituents for neighboring stations be known. The mean of the values for H and g found through these 24-hour analyses is then taken as the best answer obtainable. I believe, however, that if a continuous 7-day observation recording is available, it is better to analyse it directly, reducing to the utmost the number of hypotheses to be admitted. With this in mind I have developed another method of analysis, based also on the tidal surface, but having an entirely general character since the hypotheses to be accepted are the same as those which allowed me to establish the method I described in the International Hydrographic Review, July 1964 (Vol. XLI, No. 2). Taking advantage of the properties of the tidal surface, I will show that the computations are simpler than those of the numerical method.